Are the anticipatory trunk movements occurring during load-carrying activities protective or risky? - Padula, Roslineire Simprini; De Oliveira, Ana Beatriz; Barela, Ana Maria; Barela, Jose Angelo [UNESP]; Cote Gil Coury, Helenice Jane (Elsevier B.V., 2008)
This study evaluated anteroposterior trunk movements and the time spent on activities of load-carrying to surfaces at different heights, among experienced and inexperienced individuals. Thirty-six healthy males (16 experienced and 20 inexperienced in load-carrying) had their trunk movements recorded by an electrogoniometer while transporting boxes (7 and 15 kg) to surfaces of variable heights (low, low intermediate, high intermediate and high). Longer time was spent on trunk flexion when carrying loads to low surfaces and on trunk extension when carrying to high surfaces (p<0.05). Differences in time spent on trunk flexion/extension were identified between loads, and between groups for the heavier load. There were no differences in flexion/extension amplitudes between groups or loads. Although unnecessary flexion/extension occurring prior to a task may increase the exposure of the trunk to risky movements, the amplitudes reported here were relatively small and seemed to have occurred to facilitate the final tasks.Relevance to industryLifting devices and technological assistance are increasingly available in industrial settings. However, distribution centers and delivery services represent new demands on workers and involve an expressive amount of manual handling and carrying activities. Thus, studies on carrying strategies are necessary as they can provide guidelines for safer activities. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: carrying; handling; musculoskeletal risks